Mobility training
What you do just before your workout begins can have a big impact on what you are able to do during your workout. Many athletes prepare for a training session by carrying out some routine stretching exercises, but it's important to remember that stretching helps to improve your static (non-moving) flexibility and may not do such a good job at preparing your body to move quickly and efficiently. That's why I recommend that you focus on 'dynamic mobility exercises' before every workout. Dynamic mobility exercises during your pre-workout warm-up period prepare your body completely for the vigorous movements that make up the main part of your workout. Most sports involve forceful, strenuous activity, and mobility exercises and drills stimulate your nervous system, muscles, tendons, and joints in a very dynamic manner. Static stretching exercises, in which you're not moving around at all but are simply elongating a particular muscle or group of muscles, do have a place in your training programme, but their value and proper usage are often misunderstood.